PENGUATAN MODERASI BERAGAMA MELALUI PEACE EDUCATION GUNA MEWUJUDKAN JURNALISME DAMAI - Sidik Permana; Mursyid Setiawan (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2021)
Abstract - Diversity is a necessity that cannot be separated from human life. In order to maintain the harmony of life in this diversity, peace must be fought for by all parties, one of which is through peace education. The goal of peace education is to produce people who are wise and able to position themselves through a process of strengthening moderation. This research is based on Johan Galtung's thoughts with his concept of